Does regional anaesthesia improve outcome after surgery?. Issue 11 (November 2015) - Fischer, Barrie; Bosch, Oscar Domingo
Abstract: There is conclusive evidence that regional anaesthesia provides better postoperative analgesia than systemic opioid techniques. Regional anaesthesia also has the potential to improve the functional outcome from surgery, although proving this in a clinically relevant way is challenging; many studies are inconclusive with methodological weaknesses making comparison difficult and offering conflicting evidence. Systematic reviews offer better evidence that regional anaesthesia improves outcome but both anaesthetic and surgical practice have evolved over time, so older data may not be relevant to current practice. Regional anaesthesia improves outcome only when incorporated into a structured postoperative rehabilitation and recovery programme (enhanced recovery), using the effective analgesia provided to achieve specific targets. These targets include early mobilization, active physiotherapy and early return to enteral nutrition. Other benefits of regional anaesthesia (reduced blood loss, lower risk of thromboembolic events and duration of ileus) also contribute to a reduction in postoperative morbidity. However, unless the postoperative recovery programme is modified to incorporate these benefits into a patient's recovery, the full impact of regional anaesthesia on surgical outcome will not be realized.